2012
DOI: 10.5296/ijld.v2i2.1412
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Corporate Governance on the Insurance Firm’s Performance in Bahrain

Abstract: The importance of responsibility, accountability, transparency and fairness are raising the issues of their effect on the performance of the firm and the managers as well. This is closely related to the agency problem because corporate governance mechanisms intend to induce managers to act according to the best interest of the shareholders, which is by maximizing the firm's value and ultimately reducing agency costs. This study is a contribution to other studies conducted to examine the impact of corporate gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 7 publications
1
12
1
1
Order By: Relevance
“…Thus, hypothesis H1b is supported. This finding is consistent with previous studies that found a positive relationship between board size and Tobin`s Q either in developed countries such as Khanchel, 2007;Larmou & Vafeas, 2010;Premuroso & Bhattacharya, 2007;Sueyoshi et al, 2010 or in developing countries like Kang and Kim (2011), Khan and Javid (2011, Kyereboah-Coleman (2007, Kyereboah-Coleman andBiekpe (2006), Ll, Kankpang andOkonkwo (2012), Najjar (2012), Obiyo andLenee (2011), Swamy (2011), Uadiale (2010) and Yasser, Entebang and Mansor (2011). One probable clarification for the positive significant association between board size and Tobin`s is that this result is supported by resource dependence theory, which postulates that the board has to be more strict when it comes to monitoring of management to ensure minimal financial fraud.…”
Section: Regression Results Of Model (Based On Marketing Measure)supporting
confidence: 82%
“…Thus, hypothesis H1b is supported. This finding is consistent with previous studies that found a positive relationship between board size and Tobin`s Q either in developed countries such as Khanchel, 2007;Larmou & Vafeas, 2010;Premuroso & Bhattacharya, 2007;Sueyoshi et al, 2010 or in developing countries like Kang and Kim (2011), Khan and Javid (2011, Kyereboah-Coleman (2007, Kyereboah-Coleman andBiekpe (2006), Ll, Kankpang andOkonkwo (2012), Najjar (2012), Obiyo andLenee (2011), Swamy (2011), Uadiale (2010) and Yasser, Entebang and Mansor (2011). One probable clarification for the positive significant association between board size and Tobin`s is that this result is supported by resource dependence theory, which postulates that the board has to be more strict when it comes to monitoring of management to ensure minimal financial fraud.…”
Section: Regression Results Of Model (Based On Marketing Measure)supporting
confidence: 82%
“…The results show that board size has a significant negative impact on the performance of both sizes of firm. In line with this study Najjar (2012) study the impact of corporate governance on the insurance firm's performance in Bahrain for the period from 2005 to 2010. He found that firm size, Board size and number of block-holders have significant impact on insurance firm's performance by comparing them in relation to the return on equity.…”
Section: Corporate Governance and Financial Performancementioning
confidence: 83%
“…Likewise, Najjar (2012) confirms no statistical impact of CG on firms' financial performance in Bahrain, although Ahmed and Hamdan (2015) suggest an inverse relationship after implementing the 2011 CG reforms in Bahrain. All these studies have focused on examining the relationship between CG and firm financial value (measured mainly by ROA and ROE) rather than market value (proxied usually by Tobin's q).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 91%